2020
DOI: 10.1021/acs.accounts.0c00444
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Specificity and Proton Transfer Mechanisms in Aerosol Prenucleation Clusters Relevant to New Particle Formation

Abstract: Conspectus Atmospheric aerosol particles influence the Earth’s radiative energy balance and cloud properties, thus impacting the air quality, human health, and Earth’s climate change. Because of the important scientific and overarching practical implications of aerosols, the past two decades have seen extensive research efforts, with emphasis on the chemical compositions and underlying mechanisms of aerosol formation. It has been recognized that new particle formation (NPF) contributes up to 50% of atmospheric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 55 publications
(150 reference statements)
1
25
0
Order By: Relevance
“…While isomers 1 , 3 , and 4 may be regarded as HSO4 – ·H 2 CO 3 , isomer 2 is better recognized as H 2 SO4·HCO 3 − , which is only about 2 kJ/mol higher in energy than isomer 1 . Isomer 2 is unexpected solely from gas-phase proton affinity prediction and its stability can be attributed to the formation of two strong hydrogen bonds and highly delocalized extra electrons according to previous findings by Hou et al [ 24 , 27 , 36 , 37 , 38 ]. Such electron delocalization can be partly reflected by the highest occupied molecular orbitals (HOMOs) as presented in Figure S2 .…”
Section: Resultssupporting
confidence: 65%
See 3 more Smart Citations
“…While isomers 1 , 3 , and 4 may be regarded as HSO4 – ·H 2 CO 3 , isomer 2 is better recognized as H 2 SO4·HCO 3 − , which is only about 2 kJ/mol higher in energy than isomer 1 . Isomer 2 is unexpected solely from gas-phase proton affinity prediction and its stability can be attributed to the formation of two strong hydrogen bonds and highly delocalized extra electrons according to previous findings by Hou et al [ 24 , 27 , 36 , 37 , 38 ]. Such electron delocalization can be partly reflected by the highest occupied molecular orbitals (HOMOs) as presented in Figure S2 .…”
Section: Resultssupporting
confidence: 65%
“…Geometry optimizations of all minima and transition states on the potential energy surface of the anionic molecular complex [H 2 CO 3 •HSO 4 ] − were performed by using DFT calculations. Specifically, M06-2X functional and aug-cc-pVTZ basis set were employed, as previous studies showed that this combination could provide reliable results for hydrogen bonded, bisulfate ion-containing complexes [24,27,35,36]. Harmonic frequency analysis was conducted at the same level of theory.…”
Section: Theoretical Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“… 12 , 22 This technique has been applied to the study of deprotonated water clusters, 17 , 19 model carboxylate proton-bound dimers, 26 28 and putative aerosol nucleation clusters. 12 , 13 The structure of AHA – systems has also been investigated utilizing photoelectron spectroscopy 9 − 11 , 29 and room-temperature IR action spectroscopy. 24 , 25 …”
Section: Introductionmentioning
confidence: 99%